Mechanistic insights into charge carrier dynamics in MoSe2/CdS heterojunctions for boosted photocatalytic hydrogen evolution. (December 2020) - Yang, Xiaofei; Liu, Wei; Han, Chenhui; Zhao, Chengxiao; Tang, Hua; Liu, Qinqin; Xu, Jingsan
Abstract: It is highly desirable to design an efficient photocatalysis system via manipulating electrons migration pathways for optimal hydrogen production from water splitting. Herein, flower-like MoSe2 has been employed as the co-catalyst to couple with cubic CdS nanoparticles for the in-situ construction of MoSe2 /CdS heterojunction photocatalysts. Experimental investigations suggest that the photogenerated electrons can transfer across a space charge region between the MoSe2 /CdS through the S–Mo–Se bonding, resulting in faster charge carriers separation and hence more long-lived electrons to participate in the hydrogen evolution reaction (HER). These insights are also supported by density functional theory (DFT)-based theoretical calculation. The dynamics of the photo-excited electrons was also investigated by ultrafast transient absorption spectroscopy. Furthermore, MoSe2 can afford more active sites for absorbing the protons for H2 -evolution reactions, thereby accelerating the sluggish hydrogen evolution kinetics. Therefore, under visible-light irradiation, a remarkably enhanced photocatalytic H2 generation has been achieved in the MoSe2 /CdS heterojunction (4.7 mmol g −1  h −1 ) compared to mechanically mixed sample (3.3 mmol g −1  h −1 ) and Pt-decorated CdS (1.3 mmol g −1  h −1 ). The external quantum efficiency of the MoSe2 /CdS heterojunction toward HER has been determined to be 15.6% at 450 nm. This work not only provides a rational design for utilizing abundant elements to develop high-performance photocatalysts, but also pave the way to understand the photogenerated carriers transfer dynamics. Graphical abstract: Image 1 Highlights: MoSe2 /CdS heterojunction photocatalyst was fabricated via a facile ion-exchange method. Photocatalytic hydrogen-evolving rate over the nanocomposite is 6.3 times higher than that of pristine CdS. Highly efficient HER performance is mainly attributed to accelerated interfacial charge transfer. Charge carrier dynamics is revealed by ultrafast transient absorption spectroscopy.